1988
DOI: 10.1159/000132673
|View full text |Cite
|
Sign up to set email alerts
|

Genetic complementation analysis of ataxia telangiectasia and Nijmegen breakage syndrome: a survey of 50 patients

Abstract: Cultured cells from patients with ataxia telangiectasia (AT) or Nijmegen breakage syndrome (NBS) are hypersensitive to ionizing radiation. After radiation exposure, the rate of DN A replication is inhibited to a lesser extent than in normal cells, whereas the frequency of chromosomal aberrations is enhanced. Both of these features have been used in genetic complementation studies on a limited series of patients. Here we report the results of extended complementation studies on fibroblast strains from 50 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…However, NF-kB is not activated by CPT in AT5BI cells (compare lane 6 with lanes 8 ± 10), which are primary ®broblasts from an AT patient belonging to the pseudo-complementation group D (Jaspers et al, 1988). We measured ( Figure 3b) the activity of topoisomerase I (the target of CPT) in MRC-5 and in AT5BI cells with the DNA relaxation assay (Liu and Miller, 1981) and found a similar activity in both cell lines.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…However, NF-kB is not activated by CPT in AT5BI cells (compare lane 6 with lanes 8 ± 10), which are primary ®broblasts from an AT patient belonging to the pseudo-complementation group D (Jaspers et al, 1988). We measured ( Figure 3b) the activity of topoisomerase I (the target of CPT) in MRC-5 and in AT5BI cells with the DNA relaxation assay (Liu and Miller, 1981) and found a similar activity in both cell lines.…”
Section: Resultsmentioning
confidence: 72%
“…AT5BI, GM367, AT19IJE-F, AT20IJE-F and GM8391 are from AT patients. AT20IJE-F and AT5BI cells had been assigned to complementation groups C and D respectively (Jaspers et al, 1988) and in normal cells (Figure 6a upper panel, lanes 6 ± 7 and 10 ± 11; Figure 6b, lanes 6 ± 7 and 10 ± 11). Intriguingly, after 4 h, an increase in the levels of IkBa is observed both in normal and in AT cells, maybe resulting from NF-kB-enhanced transcription of the IkBa gene, while NF-kB activity persists in MRC-5 cells only (Figure 6a; compare lanes 4 and 8 with lane 12).…”
Section: Ikba Degradation In Normal and At ®Broblastsmentioning
confidence: 99%
“…Complementation studies after mutual fusion of cells from different patients have demonstrated the existence of 4 different AT complementation groups and 2 groups for the related Nijmegen breakage syndrome [35]. Both the clinical and the genetic heterogeneity of AT may suggest that there could be more than one AT gene at this region [33].…”
Section: Discussionmentioning
confidence: 99%
“…Radioresistant DNA synthesis is a characteristic feature of AT [9]. Recently, however, Jaspers et al [35] described variants with a relatively low cellular radiosensitivity and a normal inhibition of DNA synthesis. The very rare Nijmegen Breakage Syndrome, characterized by congenital microcephaly and mental retardation, also exhibits radioresistant DNA synthesis, as well as a high incidence of malignancy and immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Auden). Table 1 Representative examples of the contributions of D. Bootsma to the development of understanding of nucleotide excision repair Xeroderma pigmentosum and ataxia telangiectasia complementation groups [77][78][79] Chromosomal stability and NER [80] The molecular defect in the XP variant [81] Cloning of NER genes [82][83][84][85] Functional characteristics of NER genes [86][87][88] DNA repair and circadian rhythms [89] Mouse models of NER disorders [90][91][92] contributions to the identification of multiple complementation groups in NER, cloning of many of the genes involved and developing mouse models (Table 1). His contributions and those of his colleagues in the Netherlands, led to a light-hearted description of them at a 1993 Congress in Denmark as the "Dutch Army".…”
Section: Introductionmentioning
confidence: 99%